Engineered Cathode Buffer Layers for Highly Efficient Organic Solar Cells: A Review - Ram Datt (Advanced Materials Interfaces, 2022)
This article presents an in-depth insight into the most efficient cathode buffer layers (CBLs) in conventional and inverted organic solar cells (OSCs). The CBL can play a critical role in improving the short circuit current density (Jsc) and fill factor (FF) of the devices by minimizing the contact resistance and reducing charge recombination at electrode/photoactive layer interface, resulting in the efficient extraction of charge carriers and therefore improving the power conversion efficiency (PCE). This review explores CBL with respect to its effect on the physics of a device and electronic processes at the interface of CBL/photoactive layer and its impact on the overall performance of solar cells. Besides this, we have discussed in detail the role of CBL, its chemical composition, morphology, thickness, dopants, deposition conditions, etc. and their corresponding effects on the device performance in both conventional and inverted OSCs. Finally, we have summarized a few CBLs that provided the best performance and discussed their chemical structures. This article will benefit the researchers working in the domain of solar cells by providing an understanding of the CBL layers, along with their interfacial working mechanism.